Feminist poetics of the sacred : creative suspicions - Devlin-Glass, Frances; McCredden, Lyn (American Academy of Religion cultural criticism series., 2001)
This is an interdisciplinary and multicultural study of ancient and contemporary texts that encode women's spirituality. The contributors, using modern critical methods such as feminist theory, postculturalism, and the new historicisms, examine how the ideas in these texts are being reworked in different religious traditions. The volume encompasses both contemporary and historical contexts, tracing the roles, actions, writings, and beliefs of women in pre-Christian, Christian, Islamic, indigenous, and neo-pagan contexts. The book builds on three decades of feminist research into such areas as.